Postoperative morbidity following pancreatic cancer surgery is significantly associated with worse overall patient survival; systematic review and meta-analysis. (September 2021) - Mintziras, Ioannis; Wächter, Sabine; Manoharan, Jerena; Kanngiesser, Veit; Maurer, Elisabeth; Bartsch, Detlef Klaus
Abstract: Backround: The influence of postoperative morbidity on survival after potentially curative resection for pancreatic ductal adenocarcinoma (PDAC) remains unclear. Methods: Medline, Web of Science and Cochrane Library were searched for studies reporting survival in patients with and without complications, defined according to the Clavien-Dindo classification, after primary, potentially curative resection for pancreatic cancer followed by adjuvant treatment. Meta-analysis was performed using a random-effects model. Results: Fourteen retrospective cohort studies comprising a total of 7.604 patients with an overall complication rate of 40.8% (n = 3.103 patients) were included. Median overall survival for the entire patient cohort ranged from 15.5 to 24 months. Overall survival in patients with severe postoperative complications ranged from 7.1 to 37.1 months and was significantly worse compared to the overall survival in patients without severe complications ranging from 16.5 to 38.2 months. Postoperative complication rates ranged from 24.3% to 64%, severe (Clavien-Dindo ≥ III) complication rates from 4.2% to 31%. Results sufficient for meta-analysis were reported by ten studies, representing 6.028 patients. Meta-analysis showed reduced overall survival following any complication (summary adjusted HR 1.47; 95% CI 1.23–1.76, p < 0.0001). Hazard of death was 1.5 times higher in patients experiencing severe postoperative complications than in patients without severe complications (summary adjusted HR 1.45; 95% CI 1.13–1.85, p = 0.003). Conclusions: Postoperative complications after potentially curative resection of PDAC are significantly associated with worse overall patient survival. Highlights: To evaluate the influence of postoperative morbidity on survival after surgery for pancreatic ductal adenocarcinoma (PDAC). Fourteen retrospective cohort studies comprising a total of 7.604 patients were included. Results sufficient for meta-analysis were reported by ten studies, representing 6.028 patients. Meta-analysis showed reduced overall survival following any complication (HR 1.47; 95% CI 1.23-1.76, p < 0.0001). Hazard of death was 1.5 times higher in patients with severe complications (HR 1.45; 95% CI 1.13-1.85, p= 0.003).